Circadian Pharmacological Effects of Paeoniflorin on Mice With Urticaria-like Lesions - Peng, Li; Wen, Lijuan; Zhang, Jie; Zhang, Xiaotong; Wei, Qin; Guo, Jing; Zeng, Jinhao (Frontiers in Pharmacology, 2022)
Paeoniflorin (PF) is a monoterpene glucoside with various biological properties, and it suppresses allergic and inflammatory responses in a rat model of urticaria-like lesions (UL). In the present study, we treated OVA-induced mice presenting UL with PF at four circadian time points (PF dosed at ZT16, ZT22, ZT4, and ZT10) to determine the optimal administration time of PF. The pharmacological effects of PF were assessed by analyzing the scratching behavior; histopathological features; allergic responses such as immunoglobulin E (IgE), leukotriene B4 (LTB4), and histamine (HIS) release; inflammatory cell infiltration [mast cell tryptase (MCT) and eosinophil protein X (EPX)]; and mRNA levels of inflammatory cytokines such as interleukin (IL)-12, IL-6, interferon γ (IFN-γ), and IL-4. It was demonstrated that PF significantly alleviated scratching behavior and histopathological features, and ZT10 dosing was the most effective time point in remission of the condition among the four circadian time points. Moreover, PF decreased the serum levels of IgE, LTB4, and HIS, and PF dosing at ZT10 significantly alleviated the allergic conditions of UL. PF treatment reduced the number of mast cells and granules and infiltration of MCT and EPX in the skin tissues of mice with UL, and the PF dosing at ZT10 displayed the best efficacy for the treatment of UL. Furthermore, the oral administration of PF effectively decreased the inflammatory cytokine levels of IL-12 mRNA. In conclusion, different administration times of PF affected its efficacy in mice with UL. Additionally, ZT10 dosing demonstrated the best efficacy, and it might be the optimal administration time for the treatment of urticaria.